Discordant resting and hyperaemic coronary physiology among unselected patients referred for coronary angiography: a single centre experience. (14th October 2021) - Sankhesara, D; Barnes, C; Kang, S; Saraswat, A; Shiekh, I; Schultz, C; Hillis, G; Alcock, R; Spiro, J
Abstract: Background: Physiological assessment of intermediate coronary artery lesions to guide therapy is well established. Recently, the use of non-hyperaemic pressure ratios (NHPRs) has been suggested as a reliable alternative to hyperaemic assessment, such as fractional flow reserve (FFR). However certain patient / lesion subsets, including proximal lesion location, young patient age and assessment of non-LAD vessels, have been associated with discordance of resting and hyperaemic measurements which has led to some confusion over their interpretation and integration into routine clinical practice. Purpose: To evaluate the frequency of discordant resting and hyperaemic measurements among patients undergoing assessment of intermediate coronary artery stenoses, and to identify common lesion-specific features within patients with discordant data. Methods: From our coronary physiology database, we identified consecutive lesions which had been assessed between October 2020 and March 2021 with both resting (resting full-cycle ratio; RFR) and hyperaemic (wire-based FFR with peripheral adenosine) indices. Positive RFR defined as <0.89 (negative RFR >0.93, grey zone RFR 0.89–0.93). Positive FFR defined as <0.80 (negative FFR ≥0.80). Concordance between measurements was assessed: Group 1 (RFR -ve, FFR +ve: positive discordance); Group 2 (RFR -ve, FFR -ve: normal concordance), Group 3 (RFR +ve, FFR +ve: abnormal concordance) and Group 4 (RFR +ve, FFR -ve: negative discordance). Results: 100 lesions were identified as being assessed with both RFR and FFR, in 83 patients (67% male), mean age 67 (±12) years, vessel assessed; LAD 66, RCA 19, LCx 13, LMCA 1 and radial graft 1; with 45 being proximal lesions. 30 RFR measurements were in the grey zone. Of the remaining 70 lesions, 55 results (79%) were concordant (Group 2 = 31, Group 3 = 24), with 15 results (21%) being discordant (Group 1 = 3, Group 4 = 12). Negative predictive value (NPV) of RFR (for FFR <0.80) was 91%, when grey zone RFR measurements were excluded. Discordance was not related to age (69 vs 68 years, p=0.75), lesion location (proximal lesion with discordance (6/15) vs proximal lesion with concordance (27/55), p=0.91, figure 1) or non-LAD vessel (non-LAD with discordance (9/15) vs non-LAD lesion with concordance (20/55), p=0.77, figure 2). Conclusion: Overall within our patient group, there appeared to be a good association of RFR to FFR. In particular, RFR had a high NPV for an FFR <0.80. The clinical relevance of discordant measurements requires further investigation. However, our data suggest that a positive RFR (<0.89) measurement may not always correlate with a significant FFR measurement (<0.80), and the mechanism for this is unclear. Consequently, caution should be applied when including these measures in every day practice, in particular within patients with a positive RFR measurement. Funding Acknowledgement: Type of funding sources: None.